Exclusive breastfeeding in rural Western China: does father’s co-residence matter? - Jingchun Nie (BMC, 2021)
Abstract Background China suffers from a low exclusive breastfeeding rate. Though it has been proofed that paternal support benefits breastfeeding a lot, the correlation between father’s co-residence and exclusive breastfeeding in China remain undiscovered. This study is to provide population-based evidence for the association of paternal co-residence on exclusive breastfeeding in rural western China. We also attempt to detect how the process works by examining the correlation between the father’s co-residence and breastfeeding family support as well as maternal decision-making power. Methods A cross-sectional study was conducted in 13 nationally-designated poverty-stricken counties in the Qinba Mountains area in 2019. Data on breastfeeding practices, the status of fathers co-residence, breastfeeding family support, and maternal decision-making power were collected via structured questionnaires from 452 caregivers-infant pairs. Multivariate regressions were conducted to explore the correlation between paternal co-residence and exclusive breastfeeding. Results The exclusive breastfeeding (0–6 months) rate was 16% in rural western China. Fathers’ co-residence was associated with a lower exclusive breastfeeding rate (OR = 0.413, 95% CI = 0.227–0.750, P = 0.004) and the rate did not improve when the father was the secondary caregiver. Even ruling out support from grandmothers, the association was still negative. Paternal co-residence did not improve maternal perceived breastfeeding family support, neither practically nor emotionally (β =0.109, P = 0.105; β =0.011,P = 0.791, respectively) and it reduced maternal decision-making power (β = − 0.196, P = 0.007). Conclusions Fathers’ co-residence is negatively associated with the exclusive breastfeeding rates in rural western China. More skill-based practical and emotional strategies should be considered on father’s education to help them better involvement and show more respect to mothers’ decisions.